PROSEDUR HUKUM PEMBIMBINGAN KLIEN PEMASYARAKATAN - Muchamad Arif Agung Nugroho; Solihah . (SUPREMASI HUKUM, 2021)
This research makes the general public understand about the legal procedures of mentoring for clients. The problem in this research is what is the legal procedure of mentoring for clients? This research focuses on the legal procedures, so it has advantages over previous research that focus more on the system. This research uses a qualitative approach and focuses on the type of normative legal research. The types of data are statutory regulations, legal books, scientific journals, and the results of interviews and observations. Data collection techniques are documentation, observation, and interviews. In the results and discussion, there is no detailed of the legal procedures of mentoring for clients but there is a Standard Operational Procedure. In the conclution, there are 3 stages of mentoring for clients, namely (a) Initial Stage; (b) Advanced Stage; and (c) Final Stage. Key Words: Monitoring; Clients, Penitentiary